Exploration of Conceptual Understanding of Science Teachers and Students: Gap Conception of Current, Voltage in Indonesia - Tawil, Muh.; Said, Muhammad Amin; Suryansari, Kemala (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2023)
This study aimed to analyze the gap between the concepts of current and voltage between junior high school students and teachers in Indonesia. The number of samples was 720 students, class X, and 527 teachers who were selected by purposive sampling diagnostic test current, mains voltage, 30 question items valid and reliable. The results show that even with a simple circuit (one or two lamps and a battery), there are still gaps in the conception of current and voltage; if the circuit is more complicated, There will be many gaps in conception, namely: (1) consumption model, (2) local reasoning, (3) voltage source is seen as a constant current source rather than a fixed voltage source, (4) voltage difference, (5) series and parallel terms, (6) source electrons, (7) power consumption, (8) guess the answer choices, (9) the explanation does not match the correct choice.